Analisis Kesiapan Petugas Unit PKP-PK Dalam Upaya Mendukung Kelancara Operasi Di Bandar Udara Internasional Adisumarmo Solo - Yan Ardiansyah (Universitas Sains dan Teknologi Komputer, 2023)
The purpose of this research is to determine the readiness of the Airport Rescue and Fire Fighting (ARFF) unit officers in supporting the smooth operation at Adisumarmo Solo International Airport. The research was conducted from October 1, 2022 to November 30, 2022, at Adisumarmo Solo International Airport, using a qualitative research method. The study was carried out in the operational section of the ARFF unit, utilizing both secondary and primary data. This included data obtained from company documents and interviews conducted with the Operational Supervisor, Squad Leader Maintenance, and Squad Leader Operational of the ARFF unit. The research findings indicate that the ARFF unit officers have relatively good readiness in dealing with potential situations that may occur at Adisumarmo Solo Airport. However, there are still several factors that need to be considered to enhance the officers' readiness, such as improved training and increased facilities and equipment. This research is expected to provide information and recommendations to the relevant parties to improve the smooth operation of Adisumarmo Solo Airport.